EFL students’ perceptions toward the use of electronic written feedback in academic writing classes - Putri, Yohanna Amanda; Hadiyanto, Anita Kurniawati; Mali, Yustinus Calvin Gai (English Education Department, Universitas Islam Indonesia, 2024)
Feedback is one of the essential things for students to help them improve and develop their writing skills. Nowadays, the kinds of feedback are varied; a form that has often been used since the pandemic is electronic written feedback. This study aims to find out the students' perceptions toward the use of electronic written feedback. This study was conducted in the English Language Education Program at a private university in Salatiga. This study included 34 students registered in an Academic Writing class during the even semester 2023. The data for this study were gathered from semi-structured interviews and questionnaires. Both thematic analysis and statistical analysis were used to analyze the data from the interview and questionnaires. The findings revealed that the students’ attitudes toward electronic feedback were positive. Moreover, this study found weaknesses and strengths in using written feedback electronically. Practical recommendations for maximizing the potential of the electronic written feedback and directions for future research are also presented in this paper.